Intrabronchial migration of hemostatic agent through a bronchial fistula after lung transplantation: a case report - Yuya Nobori; Masaaki Sato; Yasutaka Hirata; Haruo Yamauchi; Chihiro Konoeda; Kentaro Kitano; Jun Nakajima (Surgical Case Reports)
Abstract Background A bronchial fistula is a relatively rare and potentially fatal complication after lung transplantation. Thoracic surgeons and pulmonologists often face challenges when selecting treatment options. We herein report an exceptional case of intrabronchial migration of a nonabsorbable hemostatic agent, which had been placed around the pulmonary artery at the time of lung transplantation, through a bronchial fistula. Case presentation A 61-year-old man developed respiratory distress 1 year after left single-lung transplantation for idiopathic interstitial pneumonia. Bronchoscopic examination revealed an apparent foreign body protruding from the mediastinum into the distal site of the bronchial anastomosis. The foreign body was easily removed bronchoscopically and appeared to be a hemostatic agent that had been placed during the previous lung transplantation. The patient developed a similar clinical episode and finally developed hemoptysis. Computed tomography revealed a foreign body located between the bronchus and pulmonary artery, partially protruding into the bronchial lumen. Given the possibility of a bronchopulmonary arterial fistula, surgical treatment was performed. The foreign body was located between the bronchus and left pulmonary artery and was easily removed. Multiple bronchial fistulas were found, and all were closed with direct sutures. Bypass grafting of the left pulmonary artery was then performed, initially with a homograft but eventually with an extended polytetrafluoroethylene graft. The patient was finally discharged 5 months after the surgery. Conclusion We experienced an extremely rare case of intrabronchial migration of hemostatic agents used during the previous lung transplantation through a bronchial fistula, which were successfully managed by direct bronchial closure and bypass grafting of the left pulmonary artery.